Experimental studies of thermo-mechanical characteristics of nitinol alloy springs - Kozyrskyi, V.; Bunko, V. (Energy and Automation, 2024)
The article deals with the research of heat-sensitive elements based on Nitinol material - a wire with a diameter of 1.0 mm, which in the form of springs can potentially be used with the appropriate geometric parameters in the design of a heat engine of an electric power generation system. Research allows to determine the thermomechanical characteristics of springs from this alloy, namely the study of the influence of the magnitude of the preliminary deformation of such elements on the generated force. Heat hardening of the nitinol wire was carried out at a temperature of 400 to 500 °C for 4.5 hours. The study of thermomechanical characteristics was carried out when heating a thermosensitive element (spring) in water from a temperature of 20 °C to 100 °C, force measurements were performed with a spring dynamometer. Thermosensitive elements - two springs made of Nitinol alloy - were chosen for research in this work. The paper shows the model and general view of the experimental setup for the knowledge of thermomechanical characteristics of springs.The thermomechanical characteristics of the springs at different amounts of their deformation have been constructed. Graphs are presented that show that the functional dependence of the maximum generated force on the amount of spring deformation is close to linear. The interpolation method was used in the work, the corresponding coefficients were calculated and the functional dependence was constructed. The resulting dependence allows you to increase the limits of determining the maximum generated force from the amount of spring deformation and will be necessary when modeling the characteristics of a heat engine.Experimental studies have established that a significant influence on the amount of force generated by a spring made of Nitinol alloy is determined by the amount of spring deformation.  At a spring deformation of 160 mm and a temperature of 100 oC, the generated force was 4...4.05 N, and at a deformation of 100 mm - 1.75...1.85 N.Key words: thermosensitive element, force, generation of electrical energy, nitinol, shape memory alloy